KERANGKA KONSEPTUAL UNTUK MANAJEMEN STRATEGIS PADA BANK SYARIAH INDONESIA: TINJAUAN PUSTAKA—DESKRIPTIF - Gunawan Aji; Mutiara Septi; Qorry Triyulindra; Galuh Hayuningtyas (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The development of the current era, creates opportunities and challenges for people's lives in increasingly advanced economic development. Likewise in bank financial institutions or watching banks. And by improving the quality of customer service and developing an increasingly advanced economy, the government merged 3 state-owned Islamic commercial banks to become Bank Syariah Indonesia (BSI). Which can have a positive impact in competing globally by prioritizing complete services, wider reach, and better capital. The strategy of Islamic banks must prioritize aspects of justice and sustainability and pay attention to the interests of customers and society in general. For this reason, strategic management is needed so that the policies taken are not on the wrong target. This writing uses a descriptive qualitative method which is sourced from secondary data, namely from reading materials or excerpts from books, articles, journals, or other relevant scientific works as references in this study, especially strategic management. The results can be known, for strategic management to make analysis of challenges and opportunities in order to dominate the market. With proper allocation of resources, in-depth internal and external analysis. Efeective communication, and collaboration with other functional management. Skills learned for high management are essential to ensure maintenance and succeeful growth of the company’s competitive strength in the long term.